Cascaded Rotman lens fed circular array. Issue 6 (1st March 2019) - Chepala, A.; Fusco, V.
Abstract : A single Rotman lens fed circular array requires phase shifters to beam steer, whereas a two‐cascaded Rotman lens fed circular array can beam form and beam steer by simply exciting a single Rotman lens beam port. In this Letter, the authors show how cascaded Rotman lenses feeding a circular array can use this property in order to beam steer/shape and perform retrodirective action. Experimental validation at 9.3 GHz is given.